Heteromorphic stamens are differentially attractive in Swartzia (Fabaceae). Issue 5 (9th September 2022) - Basso-Alves, João Paulo; da Silva, Rafael Ferreira; Coimbra, Gabriel; Leitão, Suzana Guimarães; de Rezende, Claudia Moraes; Bizzo, Humberto Ribeiro; Freitas, Leandro; Paulino, Juliana Villela; Mansano, Vidal de Freitas
Abstract: The division of labour hypothesis between stamens has explained the evolution of divergent functions between dimorphic stamens in the same flower. However, little is known about whether the distinct type of stamens differs in attractiveness to pollinators. Therefore, we investigate whether the two types of stamens commonly found in Swartzia have different visual and olfactory attractants. We performed observations of anthesis dynamics, registration and collection of floral visitors, measurements of reflectance of floral parts and chemical analysis of the volatile organic compounds of the floral parts of two species, S. flaemingii and S. simplex . Both species have two distinct sets of stamens: one with smaller and abundant stamens in the centre of the flower and the other with fewer but larger abaxial stamens. The sets differ in UV reflectance (only S. simplex ) and exhibit a distinct chromatic contrast. Concerning olfactory attractiveness, aliphatic compounds make up most of the odour of the two species, both whole flowers and most of their floral organs. On the other hand, only S. simplex presented apocarotenoids (as ionones) and benzenoids. Furthermore, there are differences in the proportion of volatiles emitted by the stamen in both cases, as the high proportion of sesquiterpenes among the smaller stamens compared to the larger ones. In conclusion, the two types of stamens found in S. flaemingii and S. simplex show a distinct attractiveness. In addition, our data have demonstrated diverse ways of differential attractiveness both between distinct stamens set per flower and between the two species from the same pollen flowers genus. Abstract : The stamens of the same flower can differ in how they attract pollinators. The study by Basso-Alves et al. showed that the larger and smaller stamens in the genus Swartzia have different visual and olfactory signals. More surprising is that it was possible to observe that the strategies for attracting pollinators diverge between the two species studied. These differences include various types of signals, such as a visual pattern or a substance responsible for the floral odour, present in one species but absent in the other.